University Teacher Credibility as a Strategy to Motivate Students - Alfonso Javier García; Facundo A. Froment; María Rocío Bohórquez (Springer, 2023)
Abstract University students' motivation can be affected by several factors, one being their perceptions of teacher behaviour in the classroom. This study aimed to predict university students' state motivation from their perceptions of teacher credibility. The participants were 344 students from the University of Seville. A structural equation model was used with the partial least squares method (PLS-SEM), a technique based on variance, employed to test, and validate the proposed hypotheses. The results reveal, on the one hand, a positive effect of teacher credibility on state motivation and, on the other hand, that teacher credibility has predictive power and predictive relevance for state motivation. Likewise, there is evidence of predictive validity in that teacher credibility can predict values for new cases of state motivation. Strategies are provided for a university faculty to manage their behaviour in the classroom to increase their students' state motivation, highlighting the use of PLS-SEM as a data analysis tool suitable for application in higher education.